Sosialisasi Keselamatan Dan Kesehatan Kerja Bagi Peserta Pelatihan Di BLKK Teknik Las - Sapulette, Rosa orpa; Kurmasela, Hanock; Balubun, Paulus Richardo; Tarukleme, Verdinal (Universitas Pahlawan Tuanku Tambusai, 2025)
The workplace must have K3 elements that are important for the health, safety and security of workers, K3 elements have benefits in managing risks or hazards in using equipment, machines, chemicals, heavy equipment and so on. The Neria Christian Education Foundation Community Work Training Center is engaged in the field of welding. BLK Welding has a high risk of work accidents because it is related to Fire, Electricity, Heat, and heavy equipment that can cause fire and disability to the body. For this reason, it is important to provide socialization of work safety and health by using Personal Protective Equipment (PPE) related to Welding. The method used in this service is the socialization of the use of Personal Protective Equipment in conducting training at the Welding Engineering Vocational Community Work Training Center to 16 training participants. The socialization stage consists of 3 parts, namely survey, socialization and implementation of occupational safety and health (K3)The results after the Socialization were held, Participants applied it directly during Welding training, where all Participants used all Personal Protective Equipment (PPE) completely. During the implementation carried out by the participants, none experienced a Work Accident and the use of APAR and First Aid Kits were placed in the BLK Building to anticipate Work Accidents